Abstraksi Reflektif Siswa SMP dalam Menyelesaikan Masalah Matematika Ditinjau dari Kemampuan Matematika - Bias Nadilia; Pradnyo Wijayanti (Program Studi S1 Matematika UNESA, 2023)
Reflective abstraction is a process of reflection on previously learned concepts and applied to new situations. This study aims to describe the reflective abstraction of junior high school students in solving mathematical problems in terms of mathematical ability. The source of the data in this study were three male students of class VIII SMPN 20 Surabaya who had different mathematical abilities.The results of this study indicate that students with high mathematical abilities, at the recognition level, are able to remember and identify previous activities related to the problem at hand. At the representation level, students with high mathematical abilities are able to correctly translate information into mathematical models. At the level of structural abstraction, students with high mathematical abilities are able to solve problems correctly, try new ways, and overcome difficulties when solving problems. At the level of structural awareness, students with high mathematical abilities are able to provide arguments from the results of their answers and are able to solve further problems. Students with moderate mathematical abilities, at the introductory level are able to remember previous activities related to the problem at hand. At the representation level, students are able to correctly translate information into mathematical models. At the level of structural abstraction is able to solve the problem correctly. And at the level of structural awareness, students are able to solve new problems. Meanwhile, students with low mathematical abilities are unable to solve problems. Students with low mathematical abilities still have to be guided in the process of solving problems.